Evaluation of the effectiveness of national policies of minimization of consequences COVID-19 pandemics - Okhrimenko, Oksana; Zrobok, Oleksii (Technology audit and production reserves, 2021)
The object of research is the effectiveness of the implementation of measures within the national policy to minimize the effects of the COVID-19 pandemic in individual countries. One of the most problematic places is the formation of a policy to minimize the consequences of the COVID-19 pandemic, which would take into account the specifics of the national economy, its margin of safety and aimed at achieving the goals of stabilizing negative economic trends. The pandemic has led to forced quarantine restrictions, which have had a negative impact on national economies. The inability to set up full-fledged business processes has led to rising unemployment and social tensions. An analysis of the main directions of the policy of minimizing the consequences of the pandemic of individual countries that made up the analytical sample. The main characteristics of the measures taken to minimize the effects of the pandemic, aimed at stabilizing the situation in the most crisis segments of the economy: financial assistance to small and medium-sized businesses, tax benefits, job creation and unemployment benefits, stabilization of the budget and banking system. The study used a comparative analysis of the effectiveness of the pandemic confrontation through the prism of the adopted policy by analysing the dynamics of key macroeconomic indicators. This methodological approach involves the involvement of a large database, which presents the main macroeconomic indicators of individual countries and the study of the main parameters of national policies. This ensures that links are identified and that the results of the planned activities are compared. In comparison with known similar methods, this approach allows adding to the base of comparison global indices depending on the purpose of the study and to transform its subject. In the applied aspect, the evaluation of the policy of confronting the pandemic will minimize the cost of time and resources to select and justify effective measures to minimize the negative consequences of unforeseen events and forecast economic trends.